Optimazing Financial Reporting Accuracy: The Role of Incentive Contract and Managerial Effort - Yessica Amelia; Eri Kusnanto (LPPM STIE Kasih Bangsa, 2024)
This research explores the complex relationship between managerial effort and the best incentive contracts in order to improve the accuracy of financial reporting. Finding emphasize how crucial conservative accounting policies in reducing agency conflicts and ensuring the accuracy of financial reports. According to the analysis, managerial effort plays a critical role in the collection and validation of financial data, improving openness and building stakeholder trust.The practical implications imply that by encouraging managerial discretion in information gathering and coordinating incentive contracts with shareholder interests, companies might enhance the integrity of financial reporting. Strong regulatory frameworks that encourage accountability and lessen information asymmetry in corporate governance are required by the policy implications.